Trade policy and illegal immigration - Subhayu Bandyopadhyay; Ryo Takashima (Institute for the Study of Labor (IZA), 2005)
We use a version of the Meade model to consider the effects of interdependent import tariffs in the presence illegal immigration. First, we consider the small union case and derive the Nash tariff equilibrium for two potential members of a Preferential Trade Agreement (PTA). We analyze conditions under which a movement from the Nash equilibrium to complete intra-bloc tariff elimination (FTA) is likely to be welfare augmenting. The paper also considers how reduction of the external tariff may impact the Nash equilibrium tariffs of the potential bloc members. The analysis is extended to the large union case to consider the conditions under which terms of trade of bloc members improve with respect to the non-member nation(s).
Keywords: F11; F22; 330; preferential trade agreement; illegal immigration; optimal tariff